A study of the relationship among instructional leadership behaviors of the school principal and selected school-level characteristics. - Sheppard, L. Bruce. (University of Ottawa (Canada), 1993)
This study examined the relationship among instructional leadership behaviors of the school principal and selected school-level characteristics. Instructional leadership was considered from a "broad" perspective to include behaviors that have been identified through research primarily based on a goal attainment model of effectiveness. In such a model school effectiveness is measured by student achievement on standardized tests. The selected school-level characteristics were Teacher Commitment, Professional Involvement, and Innovativeness. These have been identified as characteristics of an effective school by those adhering to a systems resource perspective. The study was conducted in the Province of Newfoundland and Labrador. Data were collected from a random sample of teachers in elementary and high schools in that province. Usable data were received from 624 teachers. The instrument employed to measure instructional leadership was the Principal Instructional Management Rating Scale (PIMRS) (Hallinger, 1992). The school-level characteristics were measured by selected scales of the School Organizational Climate Questionnaire (Giddings & Dellar, 1990). The hypotheses were as follows: Hypothesis 1. There is a positive relationship among instructional leadership behaviors exhibited by principals and the level of teacher commitment to and support of the school. Hypothesis 2. There is a positive relationship among instructional leadership behaviors exhibited by principals and the level of teacher professional involvement. Hypothesis 3. There is a positive relationship among instructional leadership behaviors exhibited by principals and the level of innovativeness in the school. Hypothesis 4 (A). School type (elementary or high) does not affect the relationship among instructional leadership behaviors exhibited by principals and teacher commitment. Hypothesis 4 (B). School type (elementary or high) does not affect the relationship among instructional leadership behaviors exhibited by principals and teacher professional involvement. Hypothesis 4 (C). School type (elementary or high) does not affect the relationship among instructional leadership behaviors exhibited by principals and teacher innovativeness. These hypotheses were tested using Multiple Regression Analysis. Only two of these hypotheses were not supported. These were hypothesis 4(B) and hypothesis 4(C). The relationship among instructional leadership behaviors of principals and the school-level characteristics of innovativeness and professional involvement were found to be statistically different for each school type. In addition to hypothesis testing, a process of modelling was employed. This process resulted in the development of five separate models. One model for Teacher Commitment for both elementary and high schools, and separate models for Innovativeness and Professional Involvement for each school type. While the instructional leadership behaviors for each model differ, all 10 behaviors of the Hallinger-Murphy conceptualization are included in at least one model. The results of this study reinforce the validity of the "broad" conceptualization of instructional leadership in the development of effective schools. It suggests that such a conceptualization is compatible with both the goal attainment and systems resource perspectives of organizational effectiveness. The findings bring into question arguments that instructional leadership is negatively related to Teacher Commitment, Professional Involvement, and Innovativeness. Finally, the developed models should be of value to practitioners and researchers as they attempt to determine leadership practices that will lead to new levels of school effectiveness.
Keywords: Education, Administration.